(untitled) (Research, Society and Development, 2021)
Home enteral nutritional therapy (HENT) is a modality of nutritional care provided at home. HENT converges on the principles of food and nutrition security (FNS); due to the act of not eating by mouth, the patient is sometimes affected by the worsening of the FNS condition. Thus, this study aims to evaluate FNS and associate it with other variables in HENT patients. This is a cross-sectional survey. Socioeconomic, clinical and nutritional data were evaluated, in addition to the FNS verification by a validated questionnaire. 45 individuals participated in the research, with a mean age of 74.56±11.86 years; 46.7% (n=21) of the households had Food and Nutritional Insecurity (FNI) and all were categorized with mild FNI. Only age and per capita income were significantly different when comparing the profiles of households with FNS and FNI (p<0.05). The preexisting FNS in the patients’ homes was not considered an independent predictor variable for the category of formula administered, even when adjusted for other variables (p>0.05). Thus, neither FNS nor family FNI were associated with the other variables presented by patients in HENT.